Pengaruh Iklan dan Perceived Security terhadap Minat Transaksi Pebayaran Berbasis e-Payment dengan Sikap sebagai Variabel Intervening pada Masyarakat di Kota Padang - Zul Fahmi; Susi Evanita (Universitas Negeri Padang, 2019)
This research aims to determine the influence of advertising and perceived security toward intention to se e-payment system with attitude as intervening variable on societies in Padang City.The sample in this research is 120 respondents who already work andlives in padang and the age between 18 until 50u years old. The sampling technique use was purposive sampling.This research was analyzed with path analysis using SPSS program version 17 . The result of this research are: (1) Advertisingand Perceived security has positive influence and significant effect toward Attitude to use e-payment system on societies in Padang city. (2) Advertising and Perceived security has not Positve and significant effect toward intention to use E-payment system on Socities in Padang city.(3) Attitude has positive and significant affect toward intention to use e-payment system on societies in Padang city. Keywords: e-payment system, advertising, perceived security, attitude, intention to use